2021
DOI: 10.1016/j.ijid.2020.09.1453
|View full text |Cite
|
Sign up to set email alerts
|

Increase in vector-borne disease reporting affecting humans and animals in Syria and neighboring countries after the onset of conflict: A ProMED analysis 2003–2018

Abstract: The protracted and violent conflict in Syria has resulted in large-scale displacement of people and destruction of health and sanitation infrastructure. The aim of this study was to examine epidemiological trends in vector-borne disease (VBD) outbreaks before and following the onset of the Syrian conflict (2011). Methods: ProMED, a digital disease surveillance tool, was queried for VBD outbreak reports affecting humans and animals in Syria and select bordering countries between 2003 and 2018. Data were normali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…This study uses available data from EWARN and COVID-19 dashboards to report trends in ILI, SARI, and SARS-CoV-2 in northern Syria, an area of protracted conflict. We noted increases in both ILI and SARI trends over the time period studied; this is consistent with other studies from Syria, which report increases in emerging and reemerging infectious diseases during the conflict ( Mowafi, 2011 ;Doganay and Demiraslan, 2016 ;Nimer, 2018 ;Raad et al, 2018 ;Tarnas et al, 2021 ). These findings support previous work in other settings where respiratory infections are important causes of excess morbidity, mortality, and case fatality among populations affected by protracted conflict ( Goniewicz et al, 2021 ;Moradi-Lakeh et al, 2018 ;Guha-Sapir and van Panhuis, 2004 ;Bellos et al, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“…This study uses available data from EWARN and COVID-19 dashboards to report trends in ILI, SARI, and SARS-CoV-2 in northern Syria, an area of protracted conflict. We noted increases in both ILI and SARI trends over the time period studied; this is consistent with other studies from Syria, which report increases in emerging and reemerging infectious diseases during the conflict ( Mowafi, 2011 ;Doganay and Demiraslan, 2016 ;Nimer, 2018 ;Raad et al, 2018 ;Tarnas et al, 2021 ). These findings support previous work in other settings where respiratory infections are important causes of excess morbidity, mortality, and case fatality among populations affected by protracted conflict ( Goniewicz et al, 2021 ;Moradi-Lakeh et al, 2018 ;Guha-Sapir and van Panhuis, 2004 ;Bellos et al, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“…The current review identified and analysed six studies on multiple infectious diseases published between January 2000 and October 2023 [ 56 61 ] (Table 8 ). Higher incidence rates of several infectious diseases were reported in Iraq [ 56 ], in the Southwest region of Cameroon [ 57 ], in Syria and neighbouring countries [ 61 ], in Jordan [ 59 ], in Ukraine [ 58 ], and in DRC [ 60 ]. During the peak years of the war in Iraq, particularly during the US military surge (2007–2009), the incidence of infectious diseases increased significantly [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“… Implemented : • Vaccine rollouts were made in a targeted fashion to displaced children • Engagement of community health workers in providing a continuity of care Suggested : Local, national, regional, and global authorities must work together to develop risk-mitigating interventions in settings with armed conflicts to preserve the delivery and utilisation of health servicesservices. Tarnas et al, 2021 [ 61 ] Syria, Turkey, Lebanon, Jordan, and Iraq, 2003–2018 Population of Syria, Turkey, Lebanon, Jordan, and Iraq • Disruption of WASH infrastructure • Mass displacement • Overcrowding in health systems that were not equipped to handle an influx of forcibly displaced people • Interruption of standard health services including routine childhood vaccination Implemented : Not mentioned Suggested : Not mentioned Malik et al, 2021 [ 59 ] Jordan, early October 2017 to January 2018 Children under-five living in Jordan • A massive influx of Syrian refugees in Jordan placed immense pressure on the country’s over-stretched resources and affected the country’s health care system with exerted demand. • People coming through conflict-driven displacement had no or low access to healthcare and lack basic healthcare facilities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations